(3GSJQGJjLjI GdHfJGLQGe hfXQjI JQjR dMd GdeTcdGJ HWQb EHOGYjI (B:s (3Odjd (B((3CfTWI(B-(3JOQjHGJ(B-(3GNJHGQGJ(B) /s - (3YHO GdYRjR, YeQh SjO UGdMs ([(3GdbGgQI(B] :s (3ecJHI GdCfLdh GdeUQjI,s, 2017)
(3LGAJ GdMGLI dgPG GdcJGH hg`h Odj`d ddCfT`WI hGdeeGQSGJ GdhGbYjI dGSJQGJjL`jI GdHfJGLQGe GdJj JQGYj GdaQhb GdaQOjI Hjf GdW`dGH, hJajO JYRjR bfGYGJ heeGQSGJ GdeYdejf djchfhG Phj aGYdjI YGdjI aj GdJOQjS, MjK Je OeL eHGOF fXQjI JQj`R eY GSJQGJjL`jI GdHfJGLQGe HgOa JfejI egGQGJ GdJacjQ hM`d GdeTcdGJ HWQb EHOGYjI hbO LGA GdcJGH eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3GSJQGJjLjI GdHfJGLQGe GdJUeje GdNeGSj GdOGFQj GdaUd GdKGfj (B: (3GSJQGJjLjI GdHfJGLQGe hfXQjI JQjR dMd GdeTcdGJ HWQjbg GdOGYjI GdaUd GdKGdK (B: (3GdYdGbI Hjf GSJQGJjLjI GdHfJGLQGe heHGOF fXQjI JQjR(B.s
(3HHdjhLQGajI (B: (3UaMI (B196-197.s
Keywords: (3fXQjI JQjRs; (3GSJQGJjLjI GdHfJGLQGes; (3Md GdeTcdGJs -- (3LhGfH faSjIs